beta-Naphthylamidase activity of the cell surface of Ehrlich ascites cells. Reversible control of enzyme activity by metal ions and thiols. - Short, A. K. (Nature Publishing Group, 1981)
Ehrlich ascites tumour cells grown in mice have a cell-surface trypsin-like neutral protease (TLNP) which is not inhibited by high-mol.-wt inhibitors of trypsin. This enzyme is inhibited by low concentrations of zinc, which may be removed by chelating agents, with the consequent return of enzymic activity. Gold, provided as the drugs aurothiomalate or auranofin, also inhibits TLNP. The gold can be removed from the enzyme by incremental addition of thiols. The mechanisms of gold transfer to the active site to cause inhibition and subsequent removal of gold with reactivation of TLNP, have been shown to be controlled by reversible thiol-exchange reactions.